THE RATE AND TIME TO FIRST READMISSION IN PATIENTS DISCHARGED WITH A DIAGNOSIS OF ACUTE DECOMPENSATED HEART FAILURE ADMITTED TO THE CARDIOLOGY DEPARTMENT, AYUB TEACHING HOSPITAL, ABBOTTABAD - Saad Shams; Imran Khan; Rukhshanda Afsar; Fatima Javed; Zia Ullah Khan; Aftab Ahmad; Mati Ullah Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Admission for heart failure poses a significant risk of readmission. Evaluating readmission rates in settings lacking chronic disease management programs could provide valuable insights to advocate for the establishment of such services. Methods: This study focused on patients admitted to the Cardiology Department of Ayub Medical Teaching Institute with acute decompensated heart failure. After excluding patients based on exclusion criteria, demographic and clinical data were recorded, including symptoms, signs, discharge medications, and readmission status within 6 months. Patients not readmitted were contacted via telephone at 1, 3, and 6 months. Readmission rates and time to first readmission or death were documented. Results: A total of 222 patients were enrolled, with 60% being males. All patients exhibited pulmonary congestion, with 85% classified as NYHA Class III or IV. Comorbidities included hypertension (59%), history of myocardial infarction (45.49%), and diabetes (38.28%). Within 6 months, 21% of patients were readmitted, and 13% died before readmission, resulting in an overall death or readmission rate of 34% at 6 months. No significant differences were observed between readmitted and non-readmitted patients regarding sex, age, creatinine levels, haemoglobin levels, sodium levels, or ejection fraction. Utilization of guideline-directed medical treatment was low. Conclusion: The high rate of readmission or death among patients admitted with acute decompensated heart failure underscores the necessity for implementing multidisciplinary care to closely monitor these patients.